The Implementation of Integrated Skills Approach in English Language Teaching at MA Darul Istiqamah Boarding School Maros - Abdullah, Ahmad Rizal (Celebes Journal of Language Studies, 2025)
This study examines the implementation of the Integrated Skills Approach (ISA) in English Language Teaching (ELT) at MA Darul Istiqamah Boarding School, Maros. The ISA emphasizes the simultaneous development of listening, speaking, reading, and writing skills in a cohesive and communicative learning environment. This approach is believed to better reflect real-world language use and improve students’ overall language competence. The study employed a quantitative research design with purposive sampling. The participants consisted of twenty Grade XI students, selected randomly from Science, Social Sciences, and Language tracks. Data were collected through pre- and post-tests, structured questionnaires, and classroom observations. Statistical analysis showed significant improvement in students’ proficiency, particularly in speaking and writing skills, after being taught using the integrated skills method. The results indicate that the Integrated Skills Approach positively impacts students’ motivation, engagement, and communicative competence. These findings have important pedagogical implications for English teaching at MA Darul Istiqamah and other similar educational institutions. The study recommends the broader application of this approach in secondary education to promote more effective and meaningful English language learning.